Strengthening digital citizenship through discourse analysis of presidential and vice-presidential candidates in the 2024 Presidential Election - Budi Mulyono; Winda Trilatifah; Moch. Ari Nasichuddin; Irwan Syambudi; Diana Trisnawati (Jurnal Civics: Media Kajian Kewarganegaraan)
With the rapid advancement of information technology and increased internet access in Indonesia, citizens' participation in the digital realm has grown substantially. Digital citizens' presence is crucial in the 2024 Presidential Election, playing a pivotal role in disseminating political information, influencing public opinion, and providing support to candidates. This study examines the digital citizens' discourse on presidential and vice-presidential candidate pairs in the 2024 election in the digital public sphere. The method of issue analysis employs topic modeling with keywords "anies muhaimin," "ganjar mahfud," and "prabowo gibran" on social media platform X. The research findings indicate that the discourse is clustered for each candidate pair. Narratives of support and optimism predominantly characterize the Anies-Muhaimin pair. The Ganjar-Mahfud pair exhibits clusters covering volunteer support, constitutional narratives, development aspirations, uniform buzzer narratives, and support from figures such as Yenny Wahid and advocacy for Palestine. The Prabowo-Gibran pair has clusters discussing support from the younger generation, political dynasty issues, PDIP reactions, and buzzer strategies with massive hashtags. Digital citizens engage in organized and diverse discourses regarding presidential and vice-presidential candidates, emphasizing the importance of understanding these dynamics to ensure responsible participation in the digital political process.